Strategi Bimbingan dan Konseling Karier Bermutu pada Sekolah Menengah Kejuruan Syuhada Banjarmasin - Jarkawi, Jarkawi; Ridhani, Akhmad Rizkhi; Susanto, Didi (Jurnal Kajian Bimbingan dan Konseling, 2017)
In order to have a clear career direction and career goals, vocational high school students have to think rationally. They need a strategy to realize the desired career dream. This study focuses on how the implementation of career guidance and counseling as well as analysis of Strength Weakness Opportunity Threat (SWOT) on the implementation of career guidance and counseling and strategies undertaken by Sekolah Menengah Kejuruan Syuhada Banjarmasin. The research method used is case study with data mining technique through observation, interview and documentation. The participants were 32 students, two school counselor, one headmaster and one deputy headmaster. The results show that: (1) the implementation of career guidance and counseling in Sekolah Menengah Kejuruan Syuhada Banjarmasin is very supportive for a quality career; (2) SWOT analysis is helpful in conducting quality career guidance and counseling services; (3) school counselor’s strategies are effective and efficient. Suggestions aimed at school counselor in order to compile and implement programs based on SWOT analysis, so they can implement a quality career guidance and counseling service.